The elaboration of a technical lexicon of Pilipino - Santiago, Alfonso O. (Philippine Journal of Linguistics, 1981)
A research project investigated intended users' attitudes toward different possibilities in the development of a scientific lexicon for Tagalog. A survey was taken of 100 college students, 100 professors, and 100 practitioners in the fields of medicine, biology, chemistry, physics, and mathematics in the Manila metropolitan area. These 300 subjects were classified into two linguistic groups: native and non-native speaking Tagalog. The focus was on their choice among these lexicon options: (1) getting the exact or near-equivalent of the English term from current Tagalog; (2) borrowing directly from English, either without spelling alteration or with spelling alteration to conform to the Abakada alphabet; (3) borrowing from Spanish without or with spelling alteration; and (4) using the Maugnayin method of the National Science Development Board, characterized by borrowing from the Philippine vernaculars, coining or deriving, or retrieving of archaic terms, especially from Tagalog. English and Tagalog versions of the questionnaire were randomly distributed to protect against context sensitivity. Each discipline's lexicon included 20 technical terms. Option 1 was the most preferred, with 3b (with spelling alteration) and 2a (without spelling alteration) competing for second place. Identical preference patterns were found in each of the discipline groups and in each population group, but the native-Tagalog/nonnative-Tagalog distinction was not significant. A procedure for developing a scientific lexicon based on these results is recommended.